Three Phases of Ethical Reflection in Educational Research: An Experience from Research on Memory and Human Rights - Carrasco-Jeldres, Karina (2024)
Introduction. Ethical reflection is a fundamental component of research. This reflection becomes particularly important when it is situated in a process of continuous and permanent questioning in the course of educational research that addresses the teaching of controversial issues in a country’s history. Aim. This study analyses ethical aspects within a doctoral research project on history professors’ perceptions regarding the approach to controversial issues in Chile’s recent history that involve acts of human rights violations. Methods. The ethical reflections of the researchers are examined through methodological self-awareness and participants’ perceptions of the development of the research process, following the steps for content analysis proposed by the Constructivist Grounded Theory. Results. The most relevant ethical aspects are identified for each of the three research phases—design, execution, and projection. Among these are the actions taken to promote freedom of dialogue to avoid re-victimization, compensation for potential inconveniences associated with debate on negative memories, and reciprocity and charity for social transformation. Conclusions. The study highlights the need to establish a dialogue of continuous ethical reflection in educational research that aims to ensure compliance with human rights and the protection of the dignity of the person.